A Study of Irrelevant Variability Normalization Based Training and Unsupervised Online Adaptation for LVCSR - Shi, Guangchuan; Shi, Yu; Huo, Qiang (Interspeech 2010, 2010)
This paper presents an experimental study of a maximum likelihood (ML) approach to irrelevant variability normalization (IVN) based training and unsupervised online adaptation for large vocabulary continuous speech recognition. A moving window based frame labeling method is used for acoustic sniffing. The IVN-based approach achieves a 10% relative word error rate reduction over an ML-trained baseline system on a Switchboard-1 conversational telephone speech transcription task.